Diagnosis and Treatment of Refractory Gastroesophageal Reflux Disease (GERD) - Selfie -; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2015)
Gastroesophageal reflux disease (GERD) was a damage in mucosal layer caused by gastric acid reflux. GERD was found about 10-20% in Western Countries and less in Asia, about 2,6-6,7%. Among different type of GERD, refractory GERD was a problem found in daily clinical practice. This terminology was used in patients with regurgitation and heartburn symptoms which is not responsive to 8 weeks proton pump inhibitor (PPI) therapy. There were several mechanisms underlying the etiology and pathophysiology of refractory GERD. In general, refractory GERD diagnosis was based on clinical findings, objective endoscopic examination, ambulatory reflux monitoring, and response to antiacid-secretion therapy. Reevaluation of patients compliance should be the first step in refractory GERD management. A further treatment strategies could be started, consist of medical and surgical therapies. A basic clinical knowledge of refractory GERD would help clinician in deciding the best approach for diagnosis and therapy.